2007
DOI: 10.1111/j.1742-1241.2007.01336.x
|View full text |Cite
|
Sign up to set email alerts
|

The relationship of body mass index to diabetes mellitus, hypertension and dyslipidaemia: comparison of data from two national surveys

Abstract: Summary The objectives of this study were to explore the relation between body mass index (BMI) and prevalence of diabetes mellitus, hypertension and dyslipidaemia; examine BMI distributions among patients with these conditions; and compare results from two national surveys. The Study to Help Improve Early evaluation and management of risk factors Leading to Diabetes (SHIELD) 2004 screening questionnaire (mailed survey) and the National Health and Nutrition Examination Surveys (NHANES) 1999–2002 (interview, cl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

28
303
0
14

Year Published

2009
2009
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 448 publications
(345 citation statements)
references
References 22 publications
28
303
0
14
Order By: Relevance
“…The finding from the previous study in the area showed the older age of the subjects had the more ASCVD risk factors [13]. The subjects in this study had the high level of BMI, and it is likely the signal of early ASCVD, higher risk of DM, hypertension, and hypercholesterolemia [18]. An investigation done in urban India showed that the earlier escalation of ASCVD risk factors at the younger age of 30-39 year [19].…”
Section: Discussionmentioning
confidence: 89%
“…The finding from the previous study in the area showed the older age of the subjects had the more ASCVD risk factors [13]. The subjects in this study had the high level of BMI, and it is likely the signal of early ASCVD, higher risk of DM, hypertension, and hypercholesterolemia [18]. An investigation done in urban India showed that the earlier escalation of ASCVD risk factors at the younger age of 30-39 year [19].…”
Section: Discussionmentioning
confidence: 89%
“…BMI itself is a strong predictor of overall mortality, with a progressive excess in mortality noted above the optimum BMI of 22.5-25 kg/m 2 , due mainly to metabolic and vascular disease [3] . Indeed, the prevalence of the metabolic comorbidities that contribute to atherosclerosis appears to increase significantly with increasing BMI [4,5] . In parallel with this trend in obesity is the perception that the prevalence of gastroesophageal reflux disease (GERD) has increased as well, currently affecting between 8% and 26% of the population in the western world [6][7][8] .…”
Section: Parallel Trends In Gastroesophageal Reflux Disease and Severmentioning
confidence: 99%
“…[8][9][10][11][12][13] Among the more prominent data sets are those of the Framingham Study, including the Framingham Offspring Study, in the United States, and the General Practice Research Database in the United Kingdom, the largest non-US database of ''anonymized'' primary care medical records. 14,15 Turning to the effects of body mass index (BMI) and obesity, Bays and colleagues 16 explored the relationships between BMI and prevalence of diabetes, hypertension, and dyslipidemia, examined BMI distributions among patients with these conditions, and compared results from 2 national surveys: (1) the screening questionnaire-based 2004 Study to Help Improve Early evaluation and management of risk factors Leading to Diabetes (SHIELD), and (2) the interview, clinical, and laboratory data of the 1999-2002 National Health and Nutrition Examination Surveys (NHANES). Bays et al found that mean BMI was virtually identical in the 2 data sets: 27.8 kg/m 2 for SHIELD and 27.9 kg/m 2 for NHANES.…”
mentioning
confidence: 99%